2016
DOI: 10.1002/j.0022-0337.2016.80.4.tb06101.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐Based Practice Knowledge, Perceptions, and Behavior: A Multi‐Institutional, Cross‐Sectional Study of a Population of U.S. Dental Students

Abstract: The aim of this study was to help inform faculty and curriculum leaders in academic dental institutions about the knowledge, skills, perceptions, and behavior of an institutionally diverse population of dental students with respect to evidencebased practice (EBP). A survey utilizing the validated Knowledge, Attitudes, Access, and Confidence Evaluation instrument developed by Hendricson et al. was conducted in 2012 with fourth-year dental students at seven geographically dispersed U.S. dental schools. The surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
22
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 30 publications
8
22
0
6
Order By: Relevance
“…Nevertheless, there were several areas of weakness that require improvement especially those related to evidencebased practice. This conforms with studies performed in different worldwide institutions where evidencebased dentistry and critical appraisal skills were lacking [14,24,26,27]. We can still argue that the attitudes and knowledge of graduates may alter after embarking into the career world and their concerns might be overcome once they integrate into their practice.…”
Section: Discussionsupporting
confidence: 85%
“…Nevertheless, there were several areas of weakness that require improvement especially those related to evidencebased practice. This conforms with studies performed in different worldwide institutions where evidencebased dentistry and critical appraisal skills were lacking [14,24,26,27]. We can still argue that the attitudes and knowledge of graduates may alter after embarking into the career world and their concerns might be overcome once they integrate into their practice.…”
Section: Discussionsupporting
confidence: 85%
“…This situation serves as an alert to the ineffective transfer of knowledge from research to clinical dental practice. 37 It is a call to the awareness that scientific evidence must be communicated to dentists or well disseminated, to enable them to provide their patients with the best possible treatment. 38,39 For this reason, continuing training education programs should be encouraged to keep dental clinicians abreast of the latest developments, and to prepare future professionals to seek out the best available scientific evidence on issues and challenges associated with DH.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey with North American dental students revealed that most of them agreed that EBD should be an integral part of the dental curriculum, as it potentially improves the quality of health care 18 . On the other hand, it also reports difficulty and lack of confidence in applying the model to the daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it also reports difficulty and lack of confidence in applying the model to the daily practice. Interestingly, the most frequent sources of information were colleague opinions, the internet, and textbooks, with rare consultations in critically appraised topics from databases such as the Cochrane Database of Systematic Reviews 18 .…”
Section: Discussionmentioning
confidence: 99%